EFFECT OF AN EDUCATIONAL PROGRAM USING DRIVER MODEL ON EFFICIENCY OF COGNITIVE REPRESENTATION AND LEARNING UNDERARM ENTRY AND LEG DIVE FROM A STANDING POSITION IN FREESTYLE WRESTLING FOR STUDENTS - Mohammed Hato Ali (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Wrestling is a combat sport that requires mastery of various techniques and strong cognitive representation to perform skills effectively. Traditional teaching methods often focus primarily on physical execution, while neglecting structured cognitive engagement that supports deeper understanding and learning transfer. Objectives. To address this gap, this study aimed to examine the effect of an educational program based on the Driver model on enhancing cognitive representation and learning of the underarm entry and leg dive techniques from a standing position in freestyle wrestling among students. Method. The research employed an experimental method involving 50 students from the College of Physical Education and Sports Sciences, University of Maysan. Participants were randomly assigned into two groups: an experimental group (n = 25), which received training using the Driver model, and a control group (n = 25), which received traditional instruction. The program lasted for eight weeks, consisting of eight educational units, with four units dedicated to each technique. Results. Findings indicated that the educational program using the Driver model significantly improved the experimental group’s ability to learn and execute the underarm entry and leg dive techniques compared to the control group. Moreover, the experimental group demonstrated higher efficiency in cognitive representation, reflecting deeper comprehension and skill retention. Conclusion. In conclusion, integrating the Driver model into wrestling instruction enhances both cognitive and technical aspects of learning. The study contributes to the field of physical education by recommending the adoption of structured cognitive-based models, such as the Driver model, in teaching wrestling techniques to optimize skill acquisition and student development.